Análisis del potencial energético del río Toachi para la generación hidroeléctrica. - Gutiérrez Jiménez, Francisco Heriberto (2016)
This article details how the primary studies are specified to establish the flow of energy power generation and principally the turbines design flow, starting from the analysis of how determine the flow of a basin and also the methods to define the runoff flow which generates the rainfalls in the basins, analyzing the kind of grounds. When the flow of the river (basin) and design flow are specified, the type of turbine to be used is determined and also define the best efficiency possible, taking into consideration the geography of the zone of the hydroelectric, the abacus help to choose the turbine in agreed to parameters like electricity potency, voltage drops and voltage. By using the above software previously, for the design house Sarapullo and Alluriquín Hydroelectric Project Toachi machines - Pilatón, it was determined that each generating station will have three turbines type Francis of vertical axis with their complementary systems for its operation which are designed to generate 254.4 megawatts (MW) using a flow of 33.33 m3/s. Keywords: flow, basin, electric power, runoff, hydroelectric, turbine.